Success Stories Developed, Indigenous Technologies Identified andInnovative Methodology Adopted by KVK Pulwama. - Misgar, F.A.; Gul, Afshan; Ara, Tabasum; Kumar, Amit (Indian Journal of Extension Education, 2010)
Success story is the essence of any institution in general and KVK's in particular. It depicts the magnitude of work culture. It is a corner stone on which the edifice of income generating activities followed up with field level demonstrations, transfer of technology skills, conducting of on farm testing / trials and other related activities of a KVK is built. In fact a KVK without success stories is like a human being drained off blood. Success stories act as a catalyst in making an institution more vibrant, work oriented and people friendly. They infuse a new life in the work culture of KVK's and make them more responsive to the needs of the people. Success stories are a gauge  for measuring the amount of success a KVK has achieved in the implementation of its workprogramme.